Meanings of quality of care: Perspectives of Portuguese health professionals and patients - Silva, S.A.; Costa, P.L.; Costa, R.; Tavares, S. M.; Leite, E. S.; Passos, A. M. (British Journal of Health Psychology, 2013)
Objectives: The main goal of this study is to explore what is meant by quality of care (QoC) by both health professionals and patients. This research also intends to compare the perspectives of nurses, doctors and patients in order to understand whether these different actors share similar views on what represents QoC. Design and methods: A qualitative study was conducted. The study consisted in 44 semi-structured individual interviews (11 doctors; 23 nurses; 10 patients) and in three focus groups (20 participants: doctors, nurses, patients). Participants were doctors, nurses and patients from several Hospitals in Portugal. Data were analysed using content analysis methodology with MaxQDA software. Results:The main content analysis' results revealed that all participants emphasize technical and interpersonal dimensions of QoC. Nevertheless, professionals stressed the availability of equipment and supplies and the conditions of health care indoor facilities. Patients focused more on their access to health services, namely the availability of health professionals, and on the health status outcome after care. In what the differences between doctors and nurses are concerned, the former tend to highlight the technical aspects of care more than the nurses, who tend to refer interpersonal aspects immediately. Conclusions:Although nowadays the importance of health care quality has become well-recognized, its definition is still complex. Given that specific aspects are more valued by certain groups than others, it is important to take in consideration all the stakeholder's perspectives when measuring QoC in order to continuously improve it in the real' settings.